Insight into radical-nonradical coupling activation pathways of peroxymonosulfate by CuxO for antibiotics degradation. (March 2023) - Tang, Jin; Yao, Siyu; Yao, Runlin; Liu, Hang; Chen, Meiqin; Zhong, Yongming; Yu, Xiaolong; Yin, Aiguo; Sun, Jianteng
Abstract: In this work, a heterogeneous catalyst of Cux O was rationally designed by using Cu-based metal organic frameworks (marked Cu-BDC) as the template, and was used to degrade tetracycline (TC) via activation of peroxymonosulfate (PMS). The optimal Cux O-350 showed excellent catalytic efficiency for TC degradation, and the reaction rate constant (0.104 min −1 ) was 8 times higher than that (0.013 min −1 ) of raw Cu-BDC. The characterization observations confirmed that Cux O-350 possessed multiple valence states (CuO and Cu2 O) and oxygen vacancies (Ov ), both of which were favorable for the activation of PMS, resulting in promoting the generation of active species in the Cux O-350 + PMS system. Different from the free radical pathway in Cu-BDC + PMS system, a radical-nonradical coupling process was detected in the Cux O-350 + PMS system, which was confirmed by quenching experiments and EPR measurements. Moreover, the toxicity prediction showed that the toxicity of degradation intermediates declined compared with TC. This work not only opened up a new strategy for the rational design and preparation of high-efficient catalysts by employing metal organic frameworks precursors, but also offered an insight into the reaction mechanism of PMS activation through a radical-nonradical coupling process catalyzed by Cux O-350 derived from Cu-BDC. Graphical abstract: Image 1 Highlights: Cux O was obtained via in situ conversion of Cu-MOFs. Cux O exhibited superior catalytic activity in comparison with Cu-MOFs. Ov and multiple valence of Cu were beneficial to PMS activation. Radical and non-radical were identified and contributed to TC degradation. TC could be effectively detoxified through Cux O + PMS system.